Blue technologies: the water- energy interrelationship and renewable energies - Kathijotes, Nicholas (My University, 2014)
The aim of Blue Economy models are to shift society from scarcity to abundance –based on what we have, and to start tackling issues that cause environmental and related problems through new and novel ways. Inland and coastal waters are investigated as ‘water resources’ that can contribute to the production of sustainable energies. In water reuse, the energy contained in used waters is also examined in order to contribute to the understanding of the water/energy relationship. Energy is needed for water cycle management; water is needed for energy production and water reuse can help to save both. Biogas production, being an important green energy issue is also examined under the scope of wastewater treatment. Significant energy savings can be achieved on major components of an ‘efficient’ wastewater treatment plant by applying novel blue economy principles. Zones where energy efficiency can be improved are explained. Marine based renewable energies are outlined based on coastal blue potentials and future world energy needs-provided that conventional energy sources are approaching exhaustion. Other general quality issues in coastal environments are presented and examined within the framework of the blue economy principle and thus suggesting actual novel sustainable management techniques.

The aim of Blue Economy models are to shift society from scarcity to abundance –based on what we have, and to start tackling issues that cause environmental and related problems through new and novel ways. Inland and coastal waters are investigated as ‘water resources’ that can contribute to the production of sustainable energies. In water reuse, the energy contained in used waters is also examined in order to contribute to the understanding of the water/energy relationship. Energy is needed for water cycle management; water is needed for energy production and water reuse can help to save both. Biogas production, being an important green energy issue is also examined under the scope of wastewater treatment. Significant energy savings can be achieved on major components of an ‘efficient’ wastewater treatment plant by applying novel blue economy principles. Zones where energy efficiency can be improved are explained. Marine based renewable energies are outlined based on coastal blue potentials and future world energy needs-provided that conventional energy sources are approaching exhaustion. Other general quality issues in coastal environments are presented and examined within the framework of the blue economy principle and thus suggesting actual novel sustainable management techniques.
Blue technologies: the water- energy interrelationship and renewable energies
Keywords: Blue economy; Sustainable energies; Biogas; Blue economy; Sustainable energies; Biogas